Japan's search for strategic security partnerships - Khandekar, Gauri; Gaens, Bart (Routledge security in Asia-Pacific series, 2018)
As tensions between China and Japan increase, including over the disputed islands in the East China Sea, Japan has adopted under Prime Minister Abe a new security posture. This involves, internally, adapting Japan's constitutional position on defence and, externally, building stronger international relationships in the Asia-Pacific region and more widely. This book presents a comprehensive analysis of these developments.